1999
DOI: 10.1007/s004390051146
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between human papillomavirus-associated cervical cancer and p53 codon 72 arginine/proline polymorphism

Abstract: High-risk mucosal human papillomaviruses encode an E6 oncoprotein, which binds the cellular p53 tumor suppressor protein, thereby marking it for degradation through the ubiquitin-mediated pathway. A common p53 polymorphism at codon-72 of exon 4 results in translation to either arginine or proline. Recently reported data suggested an increased susceptibility to E6/ubiquitin-mediated degradation of the Arg72-p53 isoform and an over-representation of the homozygous Arg72-p53 genotype in cervical cancer patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
6
0
2

Year Published

2003
2003
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 9 publications
5
6
0
2
Order By: Relevance
“…Storey et al [1998] showed that women homozygous for the Arg allele were more susceptible to develop cervical cancer than Arg/Pro heterozygous or Pro/Pro homozygous women and concluded therefore that this polymorphism might be involved in cervical carcinogenesis. However, our study shows that there is no increased risk concerning Arg/Arg genotype in the different cytological categories (P ¼ 0.336), in agreement with the most recently studies including those that used blood [Hayes et al, 1998;Kim et al, 2001;Humbey et al, 2002;Santos et al, 2005] or exfoliated cervical cells [Klaes et al, 1999;Tachezy et al, 1999;Tenti et al, 2000;Abba et al, 2003].…”
Section: Discussionsupporting
confidence: 94%
“…Storey et al [1998] showed that women homozygous for the Arg allele were more susceptible to develop cervical cancer than Arg/Pro heterozygous or Pro/Pro homozygous women and concluded therefore that this polymorphism might be involved in cervical carcinogenesis. However, our study shows that there is no increased risk concerning Arg/Arg genotype in the different cytological categories (P ¼ 0.336), in agreement with the most recently studies including those that used blood [Hayes et al, 1998;Kim et al, 2001;Humbey et al, 2002;Santos et al, 2005] or exfoliated cervical cells [Klaes et al, 1999;Tachezy et al, 1999;Tenti et al, 2000;Abba et al, 2003].…”
Section: Discussionsupporting
confidence: 94%
“…One of the most studied polymorphism is the aminoacidic variation p.Arg72Pro within the exon 4 (rs1042522:C4G), which results in a structural alteration of the protein [Pietsch et al, 2006]. The rs1042522:C4G polymorphism was associated with a higher risk of oral, nasopharyngeal, lung, thyroid, skin, cervical, prostate, bladder, gastric, colorectal, and hepatic tumors [Cenci et al, 2003;Comar et al, 2004;Ezzikouri et al, 2007;Fan et al, 2000;Granja et al, 2004;Huang et al, 2003Huang et al, , 2004Kietthubthew et al, 2003;Koushik et al, 2004;Li et al, 2004;Makni et al, 2000;Miller et al, 2002;Mitra et al, 2005;Nan et al, 2008;Perez et al, 2006;rbel-Alon et al, 2002;Shen et al, 2002;Sotamaa et al, 2005;Soulitzis et al, 2002;Starinsky et al, 2005;Szymanowska et al, 2006;Tachezy et al, 1999;teenyi-Agaba et al, 2004;Tiwawech et al, 2003;Twu et al, 2006;Whibley et al, 2009;Yang et al, 2001;Zhou et al, 2007]. Previous studies have suggested differences in the function of p53 depending on the codon 72 allele present.…”
Section: Introductionmentioning
confidence: 98%
“…Consequently, these authors noted that, in the United Kingdom, individuals homozygous for the arginine allele were about seven times more susceptible to HPV-associated tumorigenesis than proline/ arginine heterozygotes. Subsequent studies in several countries (Rosenthal et al, 1998;Lanham et al, 1998;Minaguchi et al, 1998;Hayes et al, 1998;Helland et al, 1998;Josefsson et al, 1998; Hildesheim et BR SHORT -COMMUNICATION al., 1998;Ngan et al, 1999;Tachezy et al, 1999;Dybikowska et al, 2000;Klug et al, 2001;Suárez-Rincon et al, 2002) failed to confirm this association, leading to the suspicion that in the process of HPVassociated tumorigenesis due to genotype differences at the codon 72 of p53, other factors in addition to these isoforms of p53 are important as risk factors for the development of cervical cancer.…”
Section: Introductionmentioning
confidence: 99%